2010
DOI: 10.1007/s10393-010-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infrared Camera to Understand Bats’ Access to Date Palm Sap: Implications for Preventing Nipah Virus Transmission

Abstract: Pteropus bats are commonly infected with Nipah virus, but show no signs of illness. Human Nipah outbreaks in Bangladesh coincide with the date palm sap harvesting season. In epidemiologic studies, drinking raw date palm sap is a risk factor for human Nipah infection. We conducted a study to evaluate bats' access to date palm sap. We mounted infrared cameras that silently captured images upon detection of motion on date palm trees from 5:00 pm to 6:00 am. Additionally, we placed two locally used preventative te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 31 publications
0
57
1
1
Order By: Relevance
“…They shed the virus in both saliva and urine (Reynes et al 2005, Middleton et al 2007; Pteropus bats were observed to be licking the raw date palm sap collected in the outbreak areas. Indeed, in contrast to an earlier infrared camera study in Bangladesh, where only 5% of the bats that contacted date palm sap were Pteropus bats (Khan et al 2011), when we evaluated the trees those were the sources of date palm sap consumed by cases in this outbreak, 49% of the bats that visited the tress and contacted date palm sap were Pteropus bats. There is evidence of survival of NiV in mango flesh, mango juice, pawpaw juice, and lychee juice for up to 3 days, depending upon the pH of the juice (Fogarty et al 2008).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They shed the virus in both saliva and urine (Reynes et al 2005, Middleton et al 2007; Pteropus bats were observed to be licking the raw date palm sap collected in the outbreak areas. Indeed, in contrast to an earlier infrared camera study in Bangladesh, where only 5% of the bats that contacted date palm sap were Pteropus bats (Khan et al 2011), when we evaluated the trees those were the sources of date palm sap consumed by cases in this outbreak, 49% of the bats that visited the tress and contacted date palm sap were Pteropus bats. There is evidence of survival of NiV in mango flesh, mango juice, pawpaw juice, and lychee juice for up to 3 days, depending upon the pH of the juice (Fogarty et al 2008).…”
Section: Discussionmentioning
confidence: 82%
“…We are working with local date palm sap collectors to develop socially acceptable low cost technologies to prevent bats' access to the date palm sap producing parts of the tree. Studies in Bangladesh involving local date palm sap collectors suggest that using a bamboo-skirt to cover the shaved part of the date palm tree and sap collection pot might be a practical, affordable method to prevent bats' access to the date palm sap (Nahar et al 2008, Khan et al 2011. Drinking raw date palm sap is a long-practiced tradition in Bangladesh, so public health recommendations to avoid drinking fresh date palm sap are unlikely to be universally followed.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that fruit bats frequently lick the date palm sap and occasionally urinate inside collection pots ( 14 ). In our investigation, the reported evidence of bats visiting date palm trees, the presence of bat excreta inside tari pots, the reported use of the same pot for several days without cleaning, and the accumulation of sap from multiple pots into 1 pot suggest that sap is probably contaminated with bat urine or saliva during collection and fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous NiV study reported that Pteropus spp. bats frequently feed on the shaved bark and often contaminate the sap with saliva, urine, and excreta ( 14 ). Pteropus spp.…”
mentioning
confidence: 99%
“…Infected pteropodid bats do not show clinical signs and can shed the virus via their urine (2)(3)(4)(5)(6). In the case of NiV, local outbreaks occurred regularly in India and Bangladesh since 2001 (7), where the virus was transmitted from flying foxes to humans, presumably via consumption of contaminated date palm sap (8)(9)(10). Human-to-human transmission also occurs in these countries (11,12).…”
mentioning
confidence: 99%